213k views
5 votes
F(x) = x^2 +1 G(x)=5-x

F(x) = x^2 +1 G(x)=5-x-example-1

2 Answers

3 votes

Answer:

see explanation

Explanation:

(f + g)(x)

= f(x + g(x)

= x² + 1 + 5 - x ← collect like terms

= x² - x + 6

--------------------------------

(f - g)(x)

=f(x) - g(x)

= x² + 1 - (5 - x)

= x² + 1 - 5 + x ← collect like terms

= x² + x - 4

User Shadoath
by
4.9k points
4 votes

Answer: for the question 2 I gave you the step by step explanation in the picture so you can probably better understand where you did wrong , I hope it will be helpful for you, have a nice rest of your day:)

F(x) = x^2 +1 G(x)=5-x-example-1
User Sunxs
by
4.9k points